Hubungan Tingkat Stres dan Status Gizi terhadap Keteraturan Siklus Menstruasi pada Remaja Putri - Hafsia Khairun Nisa Mokodompit; Muzayyana Muzayyana; Siti Hafidzah Mamonto (Jurnal Sehat Mandiri, 2026)
Menstrual cycle disorders are a common reproductive health problem in adolescent girls with a global prevalence of 45%. Stress levels and nutritional status are suspected to be factors that influence menstrual cycle regularity. This study aims to analyze the relationship between stress levels and nutritional status on menstrual cycle occurrence in adolescent girls at SMK Negeri 1 Kotamobagu. An observational analytical study with a cross-sectional approach was conducted on 58 female students of SMK Negeri 1 Kotamobagu selected by purposive sampling. Stress levels were measured using the DASS-21 questionnaire, nutritional status was assessed based on the WHO standard BMI/A, and menstrual cycles were categorized as regular (21-35 days) or irregular. Data analysis used the Chi-Square test. A total of 58.6% of respondents experienced irregular menstrual cycles, with polymenorrhea being the dominant disorder (43.1%). There was a significant relationship between stress levels and menstrual cycles (p=0.004), where 77.4% of adolescents with severe stress experienced irregular cycles compared to 37.0% with mild stress. Nutritional status was also significantly associated with menstrual cycles (p=0.003), with adolescents with underweight (82.4%) and overweight (76.9%) experiencing more irregular cycles than those with normal nutritional status (35.7%). Stress levels and nutritional status were significantly associated with menstrual cycles in adolescent girls. A holistic approach to adolescent reproductive health that integrates stress management and balanced nutrition is needed.